Diversity and biotechnological potential of rhizobia isolated from lima bean nodules collected at semi-arid region - Rodrigues, Tainara Louzada (2020)
The biological fixation of nitrogen (N) enables the absorption of N for plant nutrition in an efficient manner from an agronomic, economic and environmental perspective due to the savings in the use of nitrogen fertilizers, with a reduction in the cost of production and in the impacts arising from the manufacture, use indiscriminate and improper handling of these inputs. Lima bean (Phaseolus lunatus L.) is the second species of the genus Phaseolus in worldwide importance. In Brazil it is cultivated mainly in the northeast due to its rusticity in semi-arid conditions. In addition to income alternatives, lima beans are used as food, green manure and cover crops. Despite establishing symbiosis with nitrogen-fixing bacteria (NFB), there is still no inoculant for use in its cultivation. The objective of the research was to characterize phenotypically and genotypically NFB isolated from nodules of lima beans collected in the brazilian semi-arid region and to evaluate their efficiency in nitrogen nutrition of the culture under axenic conditions and in a Humic Rhodic Hapludox with and without acidity correction. Isolation and phenotypic characterization were performed in solid medium 79 and genotypic characterization was done by partial sequencing of the 16S rRNA gene. The symbiotic efficiencies were evaluated in a greenhouse under axenic conditions using tubes containing vermiculite and sand and afterwards, in pots with non-autoclaved soil with and without liming. The treatments consisted of the strains evaluated and controls using an appropriate statistical design. In total, 66 strains were isolated from the nodules. Phenotypic and genotypic diversity was found with predominance of intermediate growth strains, alkalinizing and with abundant gum production, belonging to the genus Bradyrhizobium. Liming provided increases in the development of fava beans, with interaction with some strains. Six strains of the genus Bradyrhizobium, belonging to the groups of type strains that include those of B. elkanii and B. japonicum, stood out for their biotechnological potential as inoculant to lima beans and they must be tested in the field in order to validate their indication as inoculant for this culture.